Database and expert systems applications : 31st International Conference, DEXA 2020, Bratislava, Czech Republic, September 14-17, 2020, Proceedings.: 31st International Conference, DEXA 2020, Bratislava, Czech Republic, September 14-17, 2020, Proceedings. Part I (2020) - Unknown
No abstract available